Influence of organic and inorganic fertilizers on yield and quality of sweet basil (Ocimum basilicum L.) - Suryanarayana, K Umesha, A K Nair, B Al-mansour, D Kalaivanan, M A (Journal of Spices and Aromatic Crops, 2018)
Field experiments were carried out during Kharif season of 2015 and 2016 to study the influence of FYM, inorganic fertilizers and bio-fertilizers on fresh herbage yield, quantity and quality of essential oil of sweet basil (Ocimum basilicum). Nine treatments with three replication were adopted in a randomized block design to find out the effect of different levels of N applied through FYM (100, 75 and 50% of the recommended N along with and without bio-fertilizers), recommended dose of NPK (160:80:80 kg ha-1), recommended FYM (10 t ha-1) + NPK (160:80:80 kg ha-1) and control (recommended FYM (10 t ha-1) on fresh herbage and oil yield, oil content and oil quality of sweet basil (Ocimum basilicum L.). Pooled results revealed that application of recommended FYM (10 t ha-1) along with recommended NPK (160:80:80 kg ha-1) recorded the highest fresh herbage yield (39.95 and 19.37 t ha-1), essential oil content (0.48 and 0.45%) and essential oil yield (199.7 and 107.58 kg ha-1) in the main crop and ratoon, respectively. With respect to oil quality, bio-fertilizer has a good impact on oil quality, that highest percentage of Methyl chavicol was recorded with application of recommended FYM (10 t ha-1) + recommended N through FYM along with bio fertilizers in the main crop of 2016 (63.78%) and in the ratoon (59.39 and 59.67%) of 2015 and 2016, respectively.